Physico-mathematical modelling of interaction between casein micelles and bacterial enzymes - Mancilla Canales, M; Apesteguía, A; Renata, R; Brandelli, A; Folmer Corrêad, A P; Risso, P H; Riquelme, B D (ANALES AFA, 2015)
En este trabajo se realizó una modelización fisicomatemática del proceso de coagulación enzimática utilizando elsistema constituido por micelas de caseína bovina y un pool enzimático obtenido a partir de Bacillus sp. P7aislado de Piaractus mesopotamicus. La modelización consistió en la realización de diseños factorialescompletos considerando el efecto de la temperatura, del pH y de la relación enzima/sustrato sobre el tiempo decoagulación, la dimensión fractal y la velocidad inicial del proceso de coagulación. Palabras clave: modelización fisicomatemática, micelas de caseína, proteasa bacteriana. In this paper it is shown a physicomathematical modeling of enzymatic coagulation process of casein micelles.The enzymatic pool was obtained from Bacillus sp. P7 which was isolated from Piaractus mesopotamicus.Modelling was achieved by complete design of experiments considering the effect of temperature, pH and ratioenzyme:sustrate on time of coagulation, fractal dimention and initial velocity of the coagulation process. Keywords: physicomathematical modeling, casein micelles, bacterial protease.